Effectiveness of a theory-based digital animated video intervention to reduce intention and willingness to sext among diploma students: cluster randomized controlled trial - Mansor, Norain; Ahmad, Norliza; Md Said, Salmiah; Tan, Kit-Aun; Sutan, Rosnah (JMIR Publications, 2023)
Background: Sexting refers to the exchange of sexually explicit digital content in the form of texts, photos, or videos. In recent years, sexting has become a public health concern. Surveys in Malaysia show a high prevalence of young adults engaged in sexting. Given that sexting is associated with sexual risk behavior, cyberbullying, and mental health issues, this behavior needs intervention to alleviate the resulting public health burden. However, there is a scarcity of theory-based intervention programs on the prevention of intention and willingness to sext among young adults. Objective: This study aimed to develop and implement a sexting intervention module guided by the prototype willingness model (PWM), delivered using web-based animated video, and evaluate its effectiveness among diploma students from a public higher educational institution. The primary outcomes were intention and willingness to sext, while the secondary outcomes were knowledge, attitude, perceived norms, and prototype perceptions of sexting. Methods: This 2-armed, parallel, single-blinded cluster randomized controlled trial was conducted in a public higher educational institution in the state of Melaka, Malaysia. Diploma students from 12 programs were randomly allocated into intervention and control groups. Both groups answered a self-administered web-based questionnaire assessing the outcomes at the baseline. The intervention group received a newly developed intervention module based on the PWM in the form of 5 animated videos posted on a private YouTube platform, while the control group was put on the waitlist. The intervention group was encouraged to discuss any issues raised with the researchers via WhatsApp private chat after viewing the videos. All participants were observed immediately and 3 months postintervention. Data analysis was performed with SPSS (version 26; IBM Corp). A generalized linear mixed model was used to determine the effectiveness of the intervention. Results: There were a total of 300 participants with an attrition rate of 8.3% (n=25). After adjusting for age, sex, relationship status, and the amount of time spent on the web, there were significant differences in the intention to sext (β=–.12; P=.002; Cohen d=0.23), willingness to sext (β=–.16; P<.001; Cohen d=0.40), knowledge (β=.12; P<.001; Cohen d=0.39), attitude (β=–.11; P=.001; Cohen d=0.31), perceived norms (β=–.06; P=.04; Cohen d=0.18), and prototype perceptions (β=–.11; P<.001; Cohen d=0.35) between the intervention and control groups over 3 months. Conclusions: In this study, the sexting intervention module using the PWM that was delivered via web-based animated videos was effective in reducing intention and willingness to sext as well as in improving knowledge of sexting, attitudes, perceived norms, and prototype perceptions. Therefore, relevant agencies involved in the promotion of sexual and reproductive health among young adults in Malaysia can consider the implementation of this module.